2015
DOI: 10.3389/fphar.2015.00115
|View full text |Cite
|
Sign up to set email alerts
|

Computational strategy for quantifying human pesticide exposure based upon a saliva measurement

Abstract: Quantitative exposure data is important for evaluating toxicity risk and biomonitoring is a critical tool for evaluating human exposure. Direct personal monitoring provides the most accurate estimation of a subject’s true dose, and non-invasive methods are advocated for quantifying exposure to xenobiotics. In this regard, there is a need to identify chemicals that are cleared in saliva at concentrations that can be quantified to support the implementation of this approach. This manuscript reviews the computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…It has been reported that the median unbound fraction of DTG in plasma after 16 weeks of therapy is 0.70% [ 16 ], which is similar to the median ratio of DTG saliva concentration to plasma concentration found in this study. This finding suggests that the secretion of DTG into saliva is governed mainly by passive transcellular diffusion, rather than transcellular active transport, of the unbound drug in plasma [ 17 ]. Similar observations were made in other antiretroviral drugs such as nevirapine [ 18 ], abacavir, darunavir, and raltegravir [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the median unbound fraction of DTG in plasma after 16 weeks of therapy is 0.70% [ 16 ], which is similar to the median ratio of DTG saliva concentration to plasma concentration found in this study. This finding suggests that the secretion of DTG into saliva is governed mainly by passive transcellular diffusion, rather than transcellular active transport, of the unbound drug in plasma [ 17 ]. Similar observations were made in other antiretroviral drugs such as nevirapine [ 18 ], abacavir, darunavir, and raltegravir [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to investigate the salivary clearance of 2,4-D, fulfilling a critical research gap. A previously established rat in vitro salivary system was used to investigate the transport mechanism of 2,4-D from plasma into saliva and further predict dose-dependent concentrations by modifying a recently developed computational model assessing pesticide transport into saliva (Smith et al, 2017; Timchalk et al, 2015; Weber et al, 2017). The transport of 2,4-D, a highly ionized organic acid, across the SGEC monolayer was predominantly driven by passive diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…While the transfer of 2,4-D across SGECs and salivary clearance in rats adds strength to passive diffusion acting as the primary transport mechanism in the salivary clearance of 2,4-D, it is, however, not clear whether passive transcellular transfer or paracellular ultrafiltration predominates. Small (MW ~ ≤ 300 Da), hydrophilic molecules, such as 2,4-D (MW = 221.4 Da), can transfer through tight junctions by the paracellular route (Höld et al, 1996; Timchalk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping the tear uid metabolome and building models to associate exposures to effects, as has been done for the saliva [164][165][166] , is a critical next step to tear-based biomonitoring.…”
Section: Pitfalls and Challengesmentioning
confidence: 99%